Effect of summer legume residue incorporation and fertilizer regimes on rice growth, yield, and nutrient uptake - Sunil Kumar, T.; Virdia, H. M.; Patel, K. G.; Ragi, Shridhar; Chowdhury, Manojit; Kumar, Pradeep; Elbagory, Mohssen; Omara, Alaa El-Dein; Salem, Ali; Elbeltagi, Ahmed; El-Shinawy, Doaa M. (Frontiers in Sustainable Food Systems, 2024)
In a field trial at the College Farm, NAU, Navsari (Gujarat), evaluated four main plot treatments (T1: Green gram, T2: Cowpea, T3: Dhaincha, and T4: Fallow), which were grown during the summer with three replications following a randomized block design (RCBD). Green gram and cowpea were incorporated into the soil after harvest, but dhaincha was incorporated at 50% flowering. During Kharif, each main plot was split into six smaller plots with different treatments: W1 was 100% RDF, W2 was 75% RDF, W3 was 50% RDF, W4 was 75% RDF + 25% N from FYM, W5 was 50% RDF + 50% N from FYM, and W6 was no fertilizer. The results of all 24 treatment combinations were repeated three times in a split-plot design. The analysis showed significant growth, yield attributes, grain yield, and straw yield of rice in dhaincha-incorporated plots (T3), fb greengram (T1), and cowpea (T2) plots using 100% RDF, while fallow (T4) with no fertilizer application recorded significantly lower values. SPAD meter readings of rice were higher in W4 (75% RDF + 25% N from FYM), which was at par with W1 in dhaincha-incorporated plots (75% RDF + 25% N from FYM) (W4). However, applying no fertilizer (W6) resulted in lower values. The total uptake of nitrogen and phosphorus in rice was highest when it was grown in dhaincha incorporated (T3), followed by green gram (T1), cowpea (T2) incorporated plots with the usage of 100% RDF (W1) and 75% RDF + 25% N from FYM (W4), and lower values were recorded in fallow + no fertilizer treatment (T4W6). Our study revealed that incorporating summer legumes before planting rice significantly increased plant height, tillers, grain and straw yield, and total uptake. With dhaincha, inclusion has shown a greater advantage.